KESEHATAN MENTAL MEMPENGARUHI ISTITHAAH JAMAAH HAJI LANSIA DI KABUPATEN BOYOLALI - Nurhidayati, Istianna; Murtana, Agus; Hastuti, Retno Yuli; Prayogo, Prayogo (Jurnal Profesi Keperawatan, 2025)
AbstractThe Hajj pilgrimage is a duty of humans to Allah, specifically for those who are capable (istita'ah) of traveling to the Kaaba. The purpose of this research is to determine the relationship between mental health and istita'ah among elderly Hajj pilgrims in Boyolali Regency. This research used a descriptive correlational design with a cross-sectional, using secondary data from Siskohatkes. The study employed purposive sampling, with a sample of 209 prospective Hajj pilgrims, based on inclusion criteria. The instruments used were the Self-Reported Questionnaire (SRQ 20) and the istita'ah questionnaire listed in Siskohatkes. Bivariate data analysis was conducted using the Kendall Tau test. The study results showed that 6 (2.9%) respondents were categorized as not meeting the health istita'ah for Hajj and 4 (1.9%) respondents had mental disorders. The study indicated an r-value of 0.813 and a p-value of 0.000, meaning there was a positive relationship between mental health and istita'ah among elderly Hajj pilgrims with high strength, and there was a significant relationship between mental health and istita'ah among elderly Hajj pilgrims in Boyolali Regency. To ensure that elderly prospective Hajj pilgrims maintain their mental health and health istita'ah status, it is recommended that they will deepen their religious education and spiritual preparation, keep their physical health by exercising regularly according to their abilities, maintain a healthy diet, get enough rest, undergo regular health check-ups, and maintain a positive mental attitude and motivation to stay healthy.